The ’’Do It Yourself’’ Tendon Repair Model: the Use of Silicone for Basic Tendon Surgery Training - Bogdan IONCIOAIA; Ileana Rodica MATEI (Modern Medicine)
In order to facilitate the simulation of tendon repair, especially nowadays when a trainee has limited working hours, various non-living tendon repair training models have been described in literature. One of these ingenious models consists of silicone injected into a cast such as a drinking straw, but despite its simplicity, there is no information on how various variables such as cast length and diameter or temperature and air exposure influence the production process. Therefore we have set out to research how various factors influence the manufacturing process of a silicone tendon repair model in order to easily reproduce and use it for personal training.